2002
DOI: 10.1289/ehp.02110805
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of reproductive endocrine effects in women with occupational fuel and solvent exposures.

Abstract: Hydrocarbons (HCs) found in fuels and solvents are ubiquitous in the environment, yet we know little about their effects on the endocrine system. The objective of this study was to assess the potential reproductive endocrine effects of low-dose HCs encountered by female U.S. Air Force personnel with fuel (primarily JP-8 jet fuel) and solvent exposures (n = 63). We estimated the internal dose of HCs in fuels and solvents by measuring their levels in exhaled breath, including the sum of aliphatic HCs (C6H14-C16H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 30 publications
1
46
1
1
Order By: Relevance
“…Similarly low sperm motility has been noted in 50 aircraft maintenance workers exposed to jet fuel containing benzene (Lemasters et al, 1999). Besides affecting the reproductive health of male, benzene has been reported to affect the reproductive health of female by disturbing the menstrual cycle and various hormones of reproductive system (Reutman et al, 2002). A study published from china by Huang (1991) has shown reproductive dysfunction in female workers exposed to benzene and toluene in shoe making industry.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Similarly low sperm motility has been noted in 50 aircraft maintenance workers exposed to jet fuel containing benzene (Lemasters et al, 1999). Besides affecting the reproductive health of male, benzene has been reported to affect the reproductive health of female by disturbing the menstrual cycle and various hormones of reproductive system (Reutman et al, 2002). A study published from china by Huang (1991) has shown reproductive dysfunction in female workers exposed to benzene and toluene in shoe making industry.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Though great efforts have been expended in reducing the lead level in the environment this goal is yet to be achieved in most developing countries. [22] Thus for these countries excessive Pb in the environment probably combined with hydrocarbons (HCs), [42,58] may be among the most important endocrine disruptors; probably not the bisphenols that need focus.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, media reports have indicated some service members have elected to store their semen prior to deployment because of concerns about their reproduc-reproductive health. Several environmental hazards were identified as specific reproductive health concerns in the 1991 Gulf War theater (Arfsten et al, 2001;Reutman et al, 2002;Wheeler et al, 1994). Measures intended to prevent illness in troops, including pesticides, prophylactic medications, and some immunizations, have also been considered potential reproductive health hazards (Hanke and Jurewicz, 2004;Jacobson et al, 2008a;Ryan et al, 2008a;Ryan et al, 2008b;Ryan and Seward, 2008).…”
Section: Introductionmentioning
confidence: 99%